2022
DOI: 10.3389/fbioe.2022.959512
|View full text |Cite
|
Sign up to set email alerts
|

The extended effect of adsorbed damage-associated molecular patterns and Toll-like receptor 2 signaling on macrophage-material interactions

Abstract: Implanted biomaterials elicit an immune-mediated foreign body reaction (FBR) that results in the fibrous encapsulation of the implant and can critically impact the performance of some implants. Consequently, understanding the molecular mechanisms that underpin cell-materials interactions that initiate biomaterial-induced inflammation and fibrosis is critical to improving the performance of biomaterial implants negatively impacted by the FBR. Damage-associated molecular patterns (DAMPs) are endogenous mediators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 89 publications
1
8
0
Order By: Relevance
“…The RAW 264.7 macrophage-like cell line was chosen as a model to study the DAMP-mediated cellular response. Berghaus et al reported that RAW 264.7 cells showed a similar phenotype and function to bone marrow-derived macrophages in response to TLR agonists, which is consistent with studies from our group and others. , LPS was chosen as a model DAMP, which binds TLR4, to represent damaged extracellular matrix that can act as a danger signal to recruit inflammatory cells in vivo . …”
Section: Introductionsupporting
confidence: 80%
See 4 more Smart Citations
“…The RAW 264.7 macrophage-like cell line was chosen as a model to study the DAMP-mediated cellular response. Berghaus et al reported that RAW 264.7 cells showed a similar phenotype and function to bone marrow-derived macrophages in response to TLR agonists, which is consistent with studies from our group and others. , LPS was chosen as a model DAMP, which binds TLR4, to represent damaged extracellular matrix that can act as a danger signal to recruit inflammatory cells in vivo . …”
Section: Introductionsupporting
confidence: 80%
“…Preadsorbed serum-derived proteins invoked a stronger response than cell-derived proteins, but when both were combined, the effect was enhanced. Many DAMPs signal through TLRs, specifically TLR2 or TLR4 depending on the chemistry of the DAMP. ,,, Activation of cell surface receptors beyond TLRs that recognize cell-derived DAMPs could contribute to TLR signaling. For example, NOD1 and NOD2 have been shown to recognize DAMPs from ER stress, and RAGE has been shown to recognize several of the same DAMPs as TLRs, including HMGB1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations